(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. Research on the application of information security in production is crucial for protecting data, safeguarding assets, and ensuring business continuity. At the core of information security lies the activity of protecting information by ensuring its confidentiality, availability, and integrity, as well as avoiding any compromise in critical situations. Such situations include natural, technological, and social disasters, computer failures, physical theft, and others.